Low protein corn does not influence finishing pig performance - R E Musser; C A Kerr; B T Richert; Robert D Goodband; Jim L Nelssen; Michael D Tokach (Kansas Agricultural Experiment Station Research Reports, 1993)
A total of 150 pigs was used to evaluate the effects of corn with different crude protein content on growth performance of finishing pigs. Our objective was to determine if low protein corn might result in poorer pig performance compared with pigs fed diets containing corn with a normal protein content. Control pigs were fed a diet containing corn with a crude protein content of 8.5% and formulated with soybean meal to 14.6% crude protein (.70% lysine). Pigs were also fed a diet with low crude protein corn (7.5%), which was substituted on an equal weight basis for normal corn resulting in a diet containing 13.5% crude protein. Pigs were fed a third diet using low protein corn, but formulated to 14.6% crude protein by increasing the level of soybean meal in the diet. No differences were observed in average daily gain (ADG) and average daily feed intake (ADFI) of the pigs fed any of the experimental diets; however, pigs fed the low protein corn diet without added soybean meal were the most efficient. These results indicate that low crude protein corn (7.5%) will not adversely affect finishing pig growth performance. In addition, supplemental protein apparently is not necessary when using low protein corn in diets for finishing pigs.; Swine Day, Manhattan, KS, November 18,1993
Keywords: Swine day; 1993; Kansas Agricultural Experiment Station contribution; no. 94-194-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 695; Swine; Corn; G-F; Performance